The Impact of Machine Learning on Labor Markets in EU Countries in the Context of Accelerating the Implementation of Artificial Intelligence - DINU, Mihai; PĂTÂRLĂGEANU, Simona Roxana; CIOBANU, Ghenadie; ȘOLDAN, Daniel (European Journal of Sustainable Development, 2025)
The progress of the development of artificial intelligence (AI) has led to its extensive implementation in various branches of activity. Artificial intelligence is also actively taking place on labor markets. We set out to analyze how machine learning (ML) technologies influence the structure and dynamics of economic systems, especially the labor market in EU countries. In the article we focused on the development of the implementation of artificial intelligence and machine learning, on changes in the labor market and the transformations of jobs. Artificial intelligence will lead to the disappearance of some jobs, but to the creation of new opportunities in emerging areas. Changes are occurring in the development of new skills, the adjustment of the educational system to meet the demands of labor markets influenced by AI. Problems of inequalities with social, economic, financial and educational impact will arise on the labor market. We discuss the development of strategies, proactive policies in supporting the transition of adaptation to technologies, retraining initiatives, supporting social groups and affected sectors. The challenges are significant, but the innovation brought by machine learning will contribute to economic growth, improving the quality of life, with proper management. Keywords: machine learning, artificial intelligence, labor markets, transformations of jobs, educational system